1986
DOI: 10.1093/carcin/7.11.1809
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 12-O-tetradecanoylphorbol-13-acetate-mediated epidermal ornithine decarboxylase induction and skin tumor promotion by new lipoxygenase inhibitors lacking protein kinase C inhibitory effects

Abstract: Both 2,3,5-trimethyl-6-(12-hydroxy-5,10-dodecadiynyl)-1,4-benzoquinone (AA861) and 3,4,2',4'-tetrahydroxychalcone inhibited 12-lipoxygenase of mouse epidermis. The IC50 of AA861 and 3,4,2',4'-tetrahydroxychalcone for epidermal 12-lipoxygenase were 1.9 and 0.2 microM, respectively. These agents showed very weak inhibitory actions on epidermal cyclooxygenase, with the potency of inhibition for cyclooxygenase less than 1/50 of that for lipoxygenase. Induction of epidermal ornithine decarboxylase by 12-O-tetradeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Reports have indicated that butein can suppress the proliferation of breast carcinoma, colon carcinoma, osteosarcoma, lymphoma, acute myelogenous leukemia, chronic myeloid leukemia, multiple myeloma, melanoma, and hepatic stellate cells [198][199][200]. Moreover, it was found to suppress phorbol ester-induced skin tumor formation [201,202], reduce antibodyassociated glomerulonephritis [203], and suppress liver fibrosis induced by carbon tetrachloride [204]. Furthermore, butein was also found to induce G 2 /M phase arrest and apoptosis in hepatocellular carcinoma (HCC) cells through reactive oxygen species (ROS) generation [205], suggesting that butein may have a great potential for HCC treatment.…”
Section: Buteinmentioning
confidence: 99%
“…Reports have indicated that butein can suppress the proliferation of breast carcinoma, colon carcinoma, osteosarcoma, lymphoma, acute myelogenous leukemia, chronic myeloid leukemia, multiple myeloma, melanoma, and hepatic stellate cells [198][199][200]. Moreover, it was found to suppress phorbol ester-induced skin tumor formation [201,202], reduce antibodyassociated glomerulonephritis [203], and suppress liver fibrosis induced by carbon tetrachloride [204]. Furthermore, butein was also found to induce G 2 /M phase arrest and apoptosis in hepatocellular carcinoma (HCC) cells through reactive oxygen species (ROS) generation [205], suggesting that butein may have a great potential for HCC treatment.…”
Section: Buteinmentioning
confidence: 99%
“…AA-861 Blocks the Generation of 12/15-LOX-derived Metabolites during Implantation-To address 12/15-LOX function in the pregnant uterus, we used AA-861, a coenzyme Q-like compound that is reported to inhibit LOX activity in certain tissues without affecting the other arachidonic acid-metabolizing enzymes COX-1 and COX-2 that produce various prostaglandins (21)(22)(23). To test the specificity of this inhibitor, we initially examined its effects on both COX and 12/15-LOX activities in the uterus at the time of implantation.…”
Section: Induction Of L-and E-12/15-lox Gene Expression In the Pregnamentioning
confidence: 99%
“…In vivo, AA-861 (15 µM/mouse) strongly suppressed DMBA and TPA-induced skin tumours and at 1 -30 µM dose-dependently inhibited TPA-stimulated ornithine decarboxylase (ODC) activity in mouse skin [133]. In vitro, AA-861 exerted antiproliferative activity in three human leukaemia (K562, Molt4B and HL60) and one cervical cell line (HeLa) [134].…”
Section: -Lo Inhibitorsmentioning
confidence: 99%